Peningkatan Hasil Belajar Tematik melalui Penggunaan Media Gambar pada Proses Pembelajaran Siswa Kelas IV MIS Muhammadiyah Sibatua - Rahma Maulida; Fitriani Fitriani; Muhaimin Salam; Tarman A. Arif; Idawati Fadollah; Munirah Munirah (Departement of Mathematics Education, 2023)
The purpose of this study is to describe the improvement of thematic learning outcomes through the use of image media in the learning process of grade IV MIS Muhammadiyah Sibatua students. This study used a test method on learning outcomes in each cycle. The type of Classroom Action Research is carried out in 2 cycles, each cycle consists of 4 meetings. The results of research that has been carried out using image media can improve the learning outcomes of grade IV MIS Muhammadiyah Sibatua students. With the use of image media, students are active throughout the learning process and improve learning outcomes. This improvement can be seen through the average student learning outcomes. Before applying image media, student learning outcomes averaged 6.95. And after applying image media, student learning outcomes reached an average of 9.46. Thus, the use of image media can improve student learning outcomes in class IV MIS Muhammadiyah Sibatua.